Note on the Lower Bound of Least Common Multiple - Shea-Ming Oon (Abstract and Applied Analysis)
Consider a sequence of positive integers in arithmetic progression with . Denote the least common multiple of by . We show that if , then , and we obtain optimum result on in some cases for such estimate. Besides, for quadratic sequences , we also show that the least common multiple is at least when , which sharpens a recent result of Farhi.